1984
DOI: 10.1002/zaac.19845160909
|View full text |Cite
|
Sign up to set email alerts
|

Photoelektronenspektroskopie an Niobiodiden

Abstract: Es werden die Photoelektronenspektren (AlKα, HeI) von NbI5, NbI4, Nb3I8, Nb6I11, HNb6I11, Nb6I8(CH3NH2)6, Nb6I8(C3H7NH2)6 und Nb gemessen und diskutiert. Es läßt sich zeigen, daß die Bindungsenergie BE der Niob‐Rumpfniveaus linear von der Oxydationszahl n (n = I/Nb) abhängt; für das Nb 3d5/2‐Niveau ergibt sich die Beziehung BE = 201,8 + 1,07 · n. Durch Anwendung dieser Beziehung wird der hydridartige Charakter des Wasserstoffs in HNb6I11 wahrscheinlich gemacht sowie die Zunahme der Elektronenkonzentration im N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…The second contribution to the Nb 3d peak [BE(Nb 3d 5/2 ) ¼ 205.5 eV, FWHM ¼ 1.8 eV, 25% of the overall Nb] was attributed to the presence of NbON, [31][32][33] while the high BE doublet [BE(Nb 3d 5/2 ) ¼ 207.5 eV, FWHM ¼ 2.4 eV] was ascribed to Nb 2 O 5 . [34][35][36][37][38][39][40][41][42][43] In accordance with the above observations, the presence of both niobium oxynitride and pentoxide species was attributed to the sample oxidation upon contact with the outer atmosphere. Regarding the O 1s signal, the component at BE ¼ 530.5 eV (FWHM ¼ 1.9 eV, 67.0% of the overall oxygen) could be related to Nb 2 O 5 , [38,41,42] but likely also accounted for oxygen from NbON.…”
Section: Chemical Composition: Rbs Xps and Snms Analysessupporting
confidence: 80%
“…The second contribution to the Nb 3d peak [BE(Nb 3d 5/2 ) ¼ 205.5 eV, FWHM ¼ 1.8 eV, 25% of the overall Nb] was attributed to the presence of NbON, [31][32][33] while the high BE doublet [BE(Nb 3d 5/2 ) ¼ 207.5 eV, FWHM ¼ 2.4 eV] was ascribed to Nb 2 O 5 . [34][35][36][37][38][39][40][41][42][43] In accordance with the above observations, the presence of both niobium oxynitride and pentoxide species was attributed to the sample oxidation upon contact with the outer atmosphere. Regarding the O 1s signal, the component at BE ¼ 530.5 eV (FWHM ¼ 1.9 eV, 67.0% of the overall oxygen) could be related to Nb 2 O 5 , [38,41,42] but likely also accounted for oxygen from NbON.…”
Section: Chemical Composition: Rbs Xps and Snms Analysessupporting
confidence: 80%
“…Although there is a small shift to lower electron binding energies of Mo 3d 5/2 electrons in the Q-M1 sample compared to B-M1, binding energies values of close to 233 eV in M1 [27,28] and molybdenum oxides [29,30] are attributed to Mo 6+ . Binding energies of Te 3d 5/2 (576.7 eV) and Nb 3d 5/2 (207.3 eV) core levels in Q-M1 are attributed to Te 4+ [31,32] and Nb 5+ [33,34] oxidation states. V 2p 3/2 spectra typically shows two contributions with binding energies at 516.6 eV and 517.6 eV, attributed to V 4+ and V 5+ , respectively [28,31,35,36].…”
Section: Physicochemical Properties Of Quaternarymentioning
confidence: 96%
“…Due to the additional electron coming from hydrogen atom insertion, the [HNb6I i 8] 3+ cluster core in HNb6I11 presents a VEC of 20 explaining the diamagnetic behavior observed at low temperature [40]. Photoelectron spectroscopy data indicated that insertion of hydrogen into Nb6I11 induces an increase of the oxidation state of niobium from ≈ 1.8 to ≈ 2.0 [56]. This result could be related with the weak polarization of hydrogen atom by neighboring niobium atoms highlighted by theoretical calculations performed with the self-consistent-field-X-scattered-wave (SCF-X-SW) method [57].…”
Section: Nb6i11-type (Ht and Lt Forms)mentioning
confidence: 99%